LITERATURE REVIEW: DAMPAK ANEMIA DEFISIENSI BESI PADA IBU HAMIL - Anjar Fifi Wulandari; Emi Sutrisminah; Is Susiloningtyas (Poltekkes Kemenkes Medan, 2021)
In general, the most common cause of anaemia in pregnancy is iron deficiency, which arises from maternal-fetal iron transfer, which is often exacerbated by a decrease in maternal iron stores. According to the World Health Organization (WHO), pregnancy anaemia is a global health problem that affects almost half of pregnant women. The purpose of this study was to conduct a journal review of explanatory and experimental articles published in the last 5 years starting in 2016 on deficiency anaemia in pregnancy. The research method is carried out by literature study using an electronic reference library through Medline, PubMed, NCBI, Science Direct and Proquest by investigating the impact of anaemia in pregnant women. The results literature from research in various developing and developed countries show that there is an impact that occurs when the mother had anaemia during pregnancy, namely prematurity, low birth weight, postpartum hemorrhage, maternal mortality, cesarean delivery and mental development of children. The conclusion is that there are several effects of anaemia in pregnant women, which are prematurity, low birth weight, postpartum hemorrhage, maternal mortality, cesarean delivery and children's mental development.